Speech and Its Relationship to Learning (Journal of human and social sciences, 2017)
This research paper aims to explore the fundamental relationship between speech and learning, emphasizing that speech is the cornerstone of the learning process. The study is divided into two main sections: the first addresses the concept of speech and its definition linguistically and terminologically, while the second clarifies the differences between speech, utterance, and language, along with the divisions of speech and the influence of the social environment on its acquisition. The paper relies on analyzing the views of classical linguists such as Ibn Jinni and Al-Suyuti and reviews types of speech in terms of eloquence and non-eloquence. The study concludes that speech is not merely a means of communication but an essential tool for acquiring knowledge and developing linguistic and social skills.
Keywords: Learning; Language; Utterance; Meaningful Sentence